Recent Advances in CFD for Wind and Tidal Offshore Turbines - Ferrer, Esteban; Montlaur, Adeline; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book presents novel Computational Fluid Dynamics (CFD) techniques to compute offshore wind and tidal applications. The papers in this volume are based on a mini-symposium held at ECCOMAS 2018. Computational fluid dynamics (CFD) techniques are regarded as the main design tool to explore the new engineering challenges presented by offshore wind and tidal turbines for energy generation. The difficulty and costs of undertaking experimental tests in offshore environments have increased the interest in CFD which is used to design appropriate turbines and blades, understand fluid flow physical phenomena associated with offshore environments, predict power production or characterise offshore environments amongst other topics.
Introduction -- Simple models for cross flow turbines -- Suppressing vortex induced vibrations of wind turbine blades with flaps -- Prediction of the wake behind a horizontal axis tidal turbine using LES-ALM -- Harmonic balance Navier-Stokes analysis of tidal stream turbine wave loads -- Analysis of the aerodynamic loads on a wind turbine in off-design conditions -- An algorithm for the generation of biofouled surface for applications in marine hydrodynamics -- A higher-order Chimera method based on moving least squares -- A review on two methods to detect spatio-temporal patterns in wind turbines -- Towards numerical simulation of offshore wind turbines using anisotropic mesh adaptation.
Keywords: Renewable energy sources; Fluid mechanics; Machinery; Renewable Energy; Engineering Fluid Dynamics; Machinery and Machine Elements